2019
DOI: 10.1002/pola.29375
|View full text |Cite
|
Sign up to set email alerts
|

Radical induced cationic frontal polymerization in thin layers

Abstract: Radical induced cationic frontal polymerization (FP) is a technique that allows the curing of huge epoxy parts (e.g., rotors of generators and construction composites), as well as parts with < 1 mm, within minutes instead of hours to days using only a fraction of the energy. Even harsh environmental conditions, like being submerged in water, cannot stop the FP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 19 publications
6
57
1
Order By: Relevance
“…They also showed that almost complete epoxy conversion can be achieved with a high concentration of thermal radical initiator without the need for a post curing [ 104 ]. Analogous to this study, Knaack et al [ 40 ] showed in the frontal curing of a BADGE formulation that the presence of a thermal radical initiator reduces the onset temperature of thermal curing from 190 to 110 °C. In addition, an increase in concentration of tetraphenyl ethanediol (TPED) (>1 mol %) only slightly decreases the thermal onset temperature of the curing [ 40 ].…”
Section: Chemistry Of Thermal Radical Initiatorssupporting
confidence: 67%
See 4 more Smart Citations
“…They also showed that almost complete epoxy conversion can be achieved with a high concentration of thermal radical initiator without the need for a post curing [ 104 ]. Analogous to this study, Knaack et al [ 40 ] showed in the frontal curing of a BADGE formulation that the presence of a thermal radical initiator reduces the onset temperature of thermal curing from 190 to 110 °C. In addition, an increase in concentration of tetraphenyl ethanediol (TPED) (>1 mol %) only slightly decreases the thermal onset temperature of the curing [ 40 ].…”
Section: Chemistry Of Thermal Radical Initiatorssupporting
confidence: 67%
“…It was found that both diphenyliodonium and triarylsulfonium salts based on Al anion exhibited higher polymerization rates and monomer conversion than their corresponding SbF 6 - and (BC 6 F 5 ) 4 − anions [ 56 ]. Knaack et al [ 40 ] also tested an epoxy formulation consisting of BADGE, I-Al and TPED for its effect on frontal polymerization properties. It was found that a minimum of 0.015 mol % of I-Al with 1 mol % TPED is sufficient to achieve a self-sustaining front.…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
See 3 more Smart Citations